2020
DOI: 10.1175/jpo-d-19-0163.1
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Subharmonic Instability of the Semidiurnal Internal Tides at the East China Sea Shelf Slope

Abstract: On the basis of measurements from an observing mooring system, the observational evidence of parametric subharmonic instability (PSI) that transfers energy from semidiurnal internal tides (ITs) to the subharmonic waves at the East China Sea continental shelf slope is presented for the first time. Although the mooring station is very close to the energetic semidiurnal IT generation site, about 76% of the observed shear variance is contained in the near-inertial band, which is found to have comparable upward- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…This method can effectively estimate the phase-locking between waves with different frequencies. It has been widely used to distinguish between nonlinearly coupled waves and independent waves [12,13,[72][73][74][75][76]. The bispectrum is expressed in the frequency domain as:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can effectively estimate the phase-locking between waves with different frequencies. It has been widely used to distinguish between nonlinearly coupled waves and independent waves [12,13,[72][73][74][75][76]. The bispectrum is expressed in the frequency domain as:…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous enhancement of near-inertial currents and M2f currents as well as the significant bicoherence values of the [f, M2-f] frequency indicate that this was the result of nonlinear interaction between the NIWs and M2-f waves, which reflects a mechanism of energy dissipation of internal tides and NIWs. Moreover, Yang et al [76] showed that the M2 internal tide transmits energy on a smaller scale through the parametric subharmonic instability (PSI) mechanism, revealing a complex mechanism of energy dissipation of internal tides and NIWs on the southwestern continental slope of the ECS. It is also necessary to further study the contribution of ocean mixing caused by NIWs compared with internal tides.…”
Section: Discussionmentioning
confidence: 99%
“…It has a wide continental shelf in the northwestern side which connects to a deep trough in the southeastern side through a steep continental slope. The ECS has variable types of internal waves, and previous studies have revealed characteristics of internal solitary waves [20][21][22][23] and internal tides [20,[24][25][26][27]. However, reports about near-inertial internal waves in ECS are few.…”
Section: Introductionmentioning
confidence: 99%
“…We now calculate the depth‐integrated horizontal kinetic energy (HKE) within the near‐inertial band following HKE=h1h2(u2+v2)ρ0/2dz, $\text{HKE}={\int }_{{h}_{1}}^{{h}_{2}}({u}^{\prime 2}+{v}^{\prime 2}){\rho }_{0}/2dz,$ where, ρ0 ${\rho }_{0}$ = 1,024 kg m −3 is the reference density; h 1 and h 2 are the lower and upper integration limits, respectively (Yang, Wei, & Zhao, 2020). We first extract the near‐inertial signals through bandpass filtering in the frequency space (0.9–1.15 ωf ${\omega }_{f}$) and then calculate the HKE.…”
Section: Resultsmentioning
confidence: 99%